2021
DOI: 10.1016/j.heliyon.2021.e06401
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms associated with loneliness and physical activities among graduate university students in Bangladesh: findings from a cross-sectional pilot study

Abstract: In low-resource settings like Bangladesh, there is a dearth of research on the mental health of university students. This pilot study aimed to identify the prevalence of depressive symptoms, loneliness, and physical activities as well as the associated factors of depressive symptoms among graduate students in a public university of Bangladesh. This cross-sectional study was carried out among 323 graduate students between February 2019 and May 2019. By the convenience sampling technique, data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
0
16
1
Order By: Relevance
“…After summarizing the total score obtained from the responses of the nine items, the summed score was categorized into two groups. Participants with a score of <10 were classified as having no depressive symptoms, and those who made a score of 10 were categorized as having depressive symptoms (Kundu et al, 2021;Manea et al, 2012). The reliability of the scale in the present study was high (Cronbach's α = 0.83).…”
Section: Depressive Symptomsmentioning
confidence: 56%
See 2 more Smart Citations
“…After summarizing the total score obtained from the responses of the nine items, the summed score was categorized into two groups. Participants with a score of <10 were classified as having no depressive symptoms, and those who made a score of 10 were categorized as having depressive symptoms (Kundu et al, 2021;Manea et al, 2012). The reliability of the scale in the present study was high (Cronbach's α = 0.83).…”
Section: Depressive Symptomsmentioning
confidence: 56%
“…Patient Health Questionnaire (PHQ-9), a 9-item scale, was used to assess the level of depressive symptoms. To measure the depressive symptoms, the PHQ-9 is a validated tool (Kroenke et al, 2001), which was also used in several previous studies among university students (Islam et al, 2020;Kundu et al, 2021). The PHQ-9 scale is composed of 9 individual questions, where the response for each question was coded based on a four-point Likert scale ranging from "Not at all" (0) to "Nearly every day" (3).…”
Section: Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an online self-reporting survey on the general Bangladeshi population (aged ≥ 15) found a higher prevalence of loneliness (71%) than the current study 40 . While, another study conducted among graduate students in Bangladesh reported a slightly lower prevalence of loneliness (43.3%) during the pandemic 41 . The plausible reasons for such a difference in loneliness prevalence include differences in study tools to measure loneliness, differences in the age range of participants, and online mode of survey administration.…”
Section: Discussionmentioning
confidence: 88%
“…Patient Health Questionnaire (PHQ-9), a 9-item scale, was used to assess the level of depressive symptoms. The PHQ-9 is a validated tool for measuring depressive symptoms [ 31 ], and has also been used in several previous studies among university students [ 32 , 33 , 34 ]. The PHQ-9 scale is composed of 9 individual questions, where the response for each question was coded based on a four-point Likert scale ranging from “Not at all” (0) to “Nearly every day” (3).…”
Section: Methodsmentioning
confidence: 99%